Extent of hypertension and renal injury in children surviving acute lymphoblastic leukemia. Issue 9 (2nd March 2022) - Kumar, Reeti; Mahan, John D.; Stanek, Joseph R.; Reed, Suzanne
Abstract: Background: Childhood acute lymphoblastic leukemia (ALL) fortunately has high survival rates, and understanding longer term implications of therapy is critical. In this study, we aimed to investigate kidney health outcomes by assessing the prevalence of renal dysfunction and hypertension (HTN) in children with ALL at 1–5 years after ALL diagnosis. Methods: This was a single‐center, cross‐sectional study of children with ALL who were 1–5 years post diagnosis. Glomerular filtration rate (GFR) measurements were calculated, and urine samples were collected to assess for protein/creatinine and albumin/creatinine. Blood pressure (BP) was determined by standard oscillometric technique, and children ≥6 years of age were eligible for ambulatory blood pressure monitoring (ABPM). Results: Forty‐five patients enrolled in the study, and 21 completed ABPMs. Fifteen patients (33%, 95% CI: 20%–49%) developed acute kidney injury (AKI) at least once. Thirteen (29%, 95% CI: 16%–44%) had hyperfiltration, and 11 (24%) had abnormal proteinuria and/or albuminuria. Prevalence of HTN based on clinic measurements was 42%. In the 21 ABPM patients, 14 had abnormal results (67%, 95% CI: 43%–85%), with the majority (11/21) demonstrating abnormal nocturnal dipping pattern. Conclusions: Among children with ALL, there is a high prevalence of past AKI. The presence of hyperfiltration, proteinuria, and/or albuminuria at 1–5 years after ALL diagnosis suggests real risk of developing chronic kidney disease (CKD) over time. There is a high prevalence of HTN on casual BP readings and even higher prevalence of abnormal ABPM in this group. The high prevalence of impaired nocturnal dipping by ABPM indicates an increased risk for future cardiovascular or cerebral ischemic events.